ijsr 2020
DOI: 10.36106/ijsr/5616575
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Technology Enhanced(video-Assisted) Teaching as a Teaching-Learning Tool for MBBS Final Ii Students

Abstract: Introduction: Traditional TL methods like writing on blackboard and now powerpoint presentations are increasingly becoming old fashioned, less interesting for technology savvy present generation of students. More advanced and attention seeking methods of teaching are expected by students in tandem with their excursions with technology. Here a comparative study of video-assisted teaching v/s power point presentation compared as students’ feedback after exposing them to both methods alternately.Aim and Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…This study revealed that 56% of the students liked to learn with video, which is consistent with the findings of the study by Randhawa et al, 8 where students gave their preference to video-assisted teaching, which shows that the present day technologically well-versed student wants a change from traditional teaching to technologically advanced methods of teaching which can go well with their sound knowledge of technology and internet.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study revealed that 56% of the students liked to learn with video, which is consistent with the findings of the study by Randhawa et al, 8 where students gave their preference to video-assisted teaching, which shows that the present day technologically well-versed student wants a change from traditional teaching to technologically advanced methods of teaching which can go well with their sound knowledge of technology and internet.…”
Section: Discussionsupporting
confidence: 90%
“…The findings are consistent with the findings by Nishi Roshini 5 where the post-test scores were not improved by the video-assisted teaching as compared with the traditional method indicating that traditional demonstration has an impact, which is noninferior to video-assisted teaching in improving the skill (P = 0.35028). This study revealed that 56% of the students liked to learn with video, which is consistent with the findings of the study by Randhawa et al, 8 where students gave their preference to video-assisted teaching, which shows that the present day technologically well-versed student wants a change from traditional teaching to technologically advanced methods of teaching which can go well with their sound knowledge of technology and internet.…”
Section: Discussionsupporting
confidence: 90%